Very high cycle fretting fatigue damage and crack path investigation of Nimonic 80A at elevated temperature. (March 2020) - Zhai, Yu; Huang, Zhi Yong; Zhu, Shun-Peng; Wang, Qing Yuan
Abstract: Fretting fatigue failure generally appears in turbine blades and disk tenon joint position subjected to high frequency vibration loads at elevated temperature. To study the fretting resistance of Nickel-based super alloy at high temperature, a set of fretting rig with a special heater was integrated with ultrasonic fatigue testing machine. Fretting tests with the developed apparatus were performed in very high cycle fatigue regime at elevated temperature. The initiation site and path of the cracks were analyzed via laser confocal microscope and scanning electron microscope. The cracks have a high proportion to initiate at the trailing edge of the wear zone and tend to extend to one side of the wear zone. Critical plane method with multiaxial fatigue damage parameters was used to predict the main propagation path of fatigue cracks.